Peran MIGRANT CARE dalam Mengadvokasi Kepentingan Buruh Migran Indonesia Tahun 2014-2015 - Yovi Arista; Nur Hidayat Sardini; Puji Astuti (Journal of Politic and Government Studies, 2017)
AbstractIndonesian migrant workers are still being a vulnerable group who facing a various problem, beside their contribution for the national budget income. Vulnerability situation became an implication of the unsafe labor migration processes, and also the un-fulfillment of the rights and interests of migrant workers which is being a responsibility of the state. In the age of democratization on Reformation-era, migrant workers issue and problems are being a public attention. Especially for the civil society organization that have a focus on struggle to advocates the rights and interest of Indonesian migrant workers, one of them is Migrant CARE. This research aims to see how the role of Migrant CARE as an entities of civil society in advocating the interests of Indonesian migrant workers in 2014 through 2016, and also to analyze for the supporting and obstacles factors for Migrant CARE in carrying their role.The type of research is qualitative analytical descriptive. Data was obtained from several sources such as primary data and secondary data that used as an instrument of analysis. Data collection techniques used were in-depth interviews, literature/documents study, and observation.The results showed that the role of Migrant CARE as civil society entities in 2014-2016 was effective to build a solutional efforts in advocating the interests of Indonesian migrant workers. This was manifested through the Migrant CARE's performances in their advocacy efforts, from law assistance to policy advocacy, developing a research, as well as empowering migrant workers by encourage the initiative of safe labor migration and sovereignty for migrant workers, through a social movements. Some of the supporting factors for Migrant CARE to carried their role such as the positive image, strategies and goals that were socially accepted, and support in financial and political aspects. Although, there are several obstacles factors such as the government's ray perspective to see migrant worker problems, corruption in the labor migration services, and also internal situation in the Migrant CARE’s organization. Recommendations from this research are addressed to Migrant CARE for giving more attention about their role’s sustainability, other recommendation addressed to Indonesian Government for giving more appreciation and bigger space of involvement to civil societies in policy-making processes.Keywords: Role of Civil Society, Migrant CARE, Migrant Workers